STUDY OF VEGF-A AND TGF-Β LEVELS IN BIOPTATES OF SQUAMOUS CELL CARCINOMA OF THE TONGUE AND MOUTH FLOOR MUCOSA IN POLYCHEMOTHERAPY WITH MONOCLONAL ANTIBODIES – CETUXIMAB - O. I. Kit; E. M. Frantsiyants; I. V. Neskubina; L. Yu. Vladimirova; A. A. Lyanova; Yu. A. Pogorelova; E. V. Shalashnaya; M. A. Еngibaryan; Yu. S. Sidorenko (Исследования и практика в медицине, 2019)
Aim. Study of VEGF-A and TGF-β growth factors in tumor tissue bioptates in patients with squamous cell carcinoma of the tongue and floor of the oral cavity depending on the effectiveness of polychemotherapy targeted therapy with cetuximab.Patients and methods. The study included 30 patients with squamous cell carcinoma of the tongue and mouth floor mucosa (T3-4N0-1M0). All patients received 2 cycles of therapy: cisplatin 100 mg/m2 , intravenously, day 1, 5-fluorouracil 1000 mg/m2 /day, intravenously, 96-hour continuous infusion in combination with targeted therapy (cetuximab 400 mg/ m2 on day 1 in a loading dose, then 250 mg/m2 on days 8 and 15). Patients were divided into two subgroups: target sensitivity of patients (partial regression and stabilization) n = 17 and target resistance (progression) n = 13. Levels of growth factors VEGF-A and TGF-β were determined in tumor tissue bioptates by ELISA using standard test systems (Bender Med System, Austria). Statistical processing of results was performed using the Statistica 6.0 program (Stat-Soft, 2001).Results. Polychemotherapy with cetuximab in some patients (n = 13), antitumor therapy with cetuximab did not result in statistically significant changes in levels of VEGF-A, TGF-β and the VEGF-A/TGF-β ratio compared to the initial values. In other patients (n = 17), the studied markers in tumor tissue bioptates were statistically significantly different from the initial values: VEGF-A was decreased by 1.46 times, TGF-β by 2.96 times, while the VEGF-A/TGF-β ratio was twice elevated.Conclusions. The results on levels of growth factors VEGF-A and TGF-β, as well as the VEGF-A/TGF-β ratio, are of a certain prognostic value and can be used as criteria for evaluating the efficacy of antitumor therapy in patients with squamous cell carcinoma of the tongue and mouth floor mucosa.